Production of Hard Grade Bitumen for Using in High Modulus Asphalt Concrete (Journal of University of Babylon for Engineering Sciences, 2018)
The conventional Hot Mix Asphalt (HMA) may suffer from several distress such as fatigue cracks and rutting. These distresses increase with severe climate conditions and reputation of traffic load. The High Modulus Asphalt Concrete (HMAC) designed according to the French method (EME) can be considered as one of the important solutions for these distresses. The production of HMAC requires hard grade bitumen. The current research involved a novel way to produce hard grade bitumen (asphalt binder) to be consonant with the requirements of hard grade bitumen used for a HMAC. The experimental work involved mixing polymer and cross-linking agent with conventional bitumen to get the new bitumen. Since the most concern with hard grade bitumen and HMAC is the fatigue cracks, Crumb Rubber (CR) was added to the obtained bitumen to improve the fatigue performance of the pavement. Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electronic Microscope (SEM) tests were carried out on the conventional and hard grade bitumen. The optimal value of additives was selected to meet the requirement of hard grade bitumen was 4% Novolac from weight of bitumen and 10 % of Hexamine from weight of Novolac (i.e. 0.4% of weight of bitumen), while the selected CR ratio to improve flexibility was 0.5% from weight of bitumen. FTIR and SEM test results showed that a mechanical interaction was occurring between the bitumen and the additives leads to greatly improve the mechanical properties of resulting bitumen. The obtained bitumen is satisfied to required standards and can be used for HMAC according to French method.